Karakter Berkebinekaan dalam Cerpen Ibu Guru Anakku sebagai Materi Penguatan Profil Pelajar Pancasila di SMA - Tri Yuniati; Benedictus Sudiyana*; Mukti Widayati (Balai Bahasa Sulawesi Selatan, 2023)
The purpose of this study describe the character value of the global diversity dimension the short story Ibu Guru Anakku (IGA) as material for strengthening the profile of Pancasila students in the high school phase. This study used descriptive qualitative research methods of text research type. Research data in the form of dialogue / narrative quotes that have messages with global dimension characters, the source of the data is the short story IGA by Gde Aryantha Soethama. Data collection through unit coding, recording units detected as character values with tools in the form of rubrics for classification of elements of global diversity dimensions. Data analysis is carried out by the process of reading the manuscript heuristically and hermeneutically while identifying the data in the manuscript through the matrix of indicator elements/subelements of the Pancasila student profile. The results showed that the global dimension of IGA short stories includes elements of (a) appreciation of local-regional, national, and global cultures; (b) the ability to communicate and interact interculturally, (c) reflection and responsibility for the experience of diversity, and (d) justice by believing in one's potential. Recommendation: the results of this study can be used to support/strengthen the character material profile of Pancasila students at the high school level through a holistic approach, even for students in universities. AbstrakTujuan penelitian ini mendeskripsikan nilai karakter dimensi berkebinekaan global pada cerpen Ibu Guru Anakku (IGA) sebagai materi penguatan profil pelajar Pancasila fase SMA. Penelitian ini menggunakan metode penelitian kualitatif deskriptif jenis penelitian teks. Data penelitian berupa kutipan dialog/narasi yang memiliki pesan karakter berdimensi berkebinekaan global. Sumber data adalah cerpen IGA karya Gde Aryantha Soethama. Pengumpulan data melalui pengkodean unit, pencatatan unit yang dideteksi sebagai nilai karakter dengan alat bantu berupa rubrik klasifikasi elemen-elemen dimensi berkebinekaan global. Analisis data dilakukan dengan proses pembacaan naskah secara heuristik dan hermeneutik sambil mengidentifikasi data dalam naskah melalui matrik indikator elemen/subelemen profil pelajar Pancasila. Hasil penelitian menunjukkan karakter berdimensi berkebinekaan global cerpen IGA mencakupi elemen: (a) penghargaan terhadap budaya lokal-regional, nasional, dan global; (b) kemampuan berkomunikasi dan berinteraksi antarbudaya, (c) refleksi dan tanggung jawab terhadap pengalaman kebinekaan, dan (d) berkeadilan dengan percaya pada potensi diri. Rekomendasi: hasil penelitian ini dapat digunakan untuk mendukung/menguatkan materi karakter profil pelajar Pancasila tingkat SMA melalui pendekatan holistis, bahkan untuk mahasiswa di Perguruan Tinggi.